Performativity of Homosexual Identity in Novel “They Both Die at The End”: A Queer Theory Analysis of Literature - Refomia, Meidina; Apriliani Muslimah, Olivia; Chandra, Septian Adi; Izfadllillah, Thesa (Centre for Literary and Cultural Studies, 2025)
This study uses Judith Butler's queer theory and also involves the concept of mental attitudes and mental functions by Carl Gustav Jung. Previous research has focused mainly on providing an overview of some studies that use ideas such as gender performativity and literary psychology to examine homosexual behavior and identification in films and novels. Meanwhile, this research discussing homosexual identity in the novel 'They Both Die at The End' by Adam Silvera is very restricted. Thus, this research is intended to investigate the representation of homosexual identity and also the factors that cause homosexuality in the characters of the novel. This research used qualitative research, and the data collection technique in this study uses reading and note-taking techniques. The results of this study show that the formation of homosexual identity in this novel is shown by performative actions, which are influenced by social interactions, conversations, emotional experiences, and the characteristics of the main characters.